(untitled) (Sains Humanika, 2025)
Online purchasing is one of the pivotal trading methods worldwide. Hence, it is vital to comprehend the impact of psychological factors on consumers’ online purchase intention. This study aims to determine the impact of psychological factors which are perceived of usefulness, perceived ease of use and trust on consumers’ online purchase intention among undergraduate students in higher learning institutions. This study also explores the level of psychological factors among undergraduate students. Quantitative research approach has been adapted in this study by distributing 102 sets of questionnaires to the respondents who have engaged in online purchasing before. The findings discovered that dimension trust does have a positive significant impact on consumers’ online purchase intention while perceived ease of use and perceived of usefulness is insignificant. The significance of the study is to develop understanding on the impact of psychological factors on consumers’ online purchase intention. It is also hoped that the findings of this study will contribute to government agencies, E-commerce retailers as well as researchers in the field.